Pengaruh Marketing Brand Pakaian di Instagram terhadap Niat Beli Masyarakat di Kota Batam - Vivien Christy Apriyanti; Andre Jonathan Harahap; Bryan Tandian; Pangestu; Viona Angelina Herwanto (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
Instagram’s popularity is used by many clothing brands in Indonesia to market their products. Marketing itself is needed to increase product sales. This study aims to determine the influence of clothing brand marketing on Instagram on people's buying intentions in Batam City. The quantitative research was done by disseminating online questionnaires to the people of Batam City with different age ranges and managed to collect 380 respondents. The research data were analyzed by SEM method, using SPSS and AMOS. The results of the study prove that marketing carried out by clothing brands can make customers more familiar with and remember the brand and also influence customers to disseminate the brand. However, marketing clothing brands on Instagram does not necessarily affect people's buying intentions. This is because there are various other factors that influence a person's decision to buy clothes. To increase someone's purchase intention, apart from hoping for marketing, clothing brands need to keep an eye on their products’ quality.